Effect of COVID-19 Pandemic on Emergency Department Admissions and Outcome - Tiwari, Jagannath; Paudel, Pramod; Adhikari, Sujan; Lamichhane, Sharmila; Basnet, Anjali; Subedi, Kirtipal; Bhattarai, Pratiksha; Paudel, Prajwal (Journal of Nepal Health Research Council, 2023)
Background: Emergency Department admissions have changed significantly during the COVID-19 pandemic. Understanding this variation may play a crucial role in rearranging hospital resources for better outcome. In this study, we aimed to assess the impact of COVID-19 pandemic on emergency department admission and outcome.Methods: This is a cross-sectional retrospective study conducted at Bharatpur Hospital, Nepal comparing pre- pandemic data of the 4 months (March 24 to July 21, 2019) with the initial 4 months of the pandemic (March 24 to July 21, 2020). Results: Admission in emergency ward decreased during covid period among female admission (47%vs43%), age-group(0-14)(18%vs12%), Dalit(17%vs11%) p<0.0001.Diagnosis increased during covid for acute abdomen(11%vs13%), animal and insect bite(10%vs13%), psychiatric illness(2%vs6%),poisoning and drug over dose(0.9%vs2.6%)(p<0.0001).The odds for referral(cOR 3.62,95% CI:2.70-4.84), Left against medical advice(cOR 6.03,95% CI:.06-8.94) and death(cOR 3.28,95% CI:1.64-6.68) increased during the covid respectively.Conclusions: There was decrease in rates of emergency department utilization during the Covid-19 pandemic. Admissions due to trauma, gastrointestinal, respiratory, neurological, musculoskeletal and coronary artery disease showed a decline whereas psychiatric disorders, diabetes and hypertension, animal and insect bites cases increased. Overall, mortality rate was increased.Keywords: Admission; Covid-19; emergency department